2015
DOI: 10.1038/hr.2015.82
|View full text |Cite
|
Sign up to set email alerts
|

Impact of irbesartan, an angiotensin receptor blocker, on uric acid level and oxidative stress in high-risk hypertension patients

Abstract: Hyperuricemia is a known cardiovascular risk factor. The angiotensin II receptor blocker (ARB) losartan is known to decrease serum uric acid (UA) level. A recent in vitro study demonstrated a strong interaction between irbesartan and UA transporters that exceeded that of losartan. The purpose of the present study was to evaluate the hypouricemic effect of irbesartan in a clinical setting. A total of 40 high-risk hypertensive outpatients with coronary artery disease, cerebrovascular disease and/or diabetes comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
2
22
0
2
Order By: Relevance
“…Similar findings were reported in animal and human studies, showing decreased serum uric acid levels in asthma patients according to disease severity . The relationship between uric acid, the final product of purine metabolism, inflammation and oxidative stress remains controversial, with studies showing high uric acid concentrations inducing inflammation and oxidative stress, resulting in apoptosis . However, increasing studies showed uric acid as a candidate asthma‐specific biomarker based on its antioxidative roles in decreasing ROS and preventing oxidative damage .…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings were reported in animal and human studies, showing decreased serum uric acid levels in asthma patients according to disease severity . The relationship between uric acid, the final product of purine metabolism, inflammation and oxidative stress remains controversial, with studies showing high uric acid concentrations inducing inflammation and oxidative stress, resulting in apoptosis . However, increasing studies showed uric acid as a candidate asthma‐specific biomarker based on its antioxidative roles in decreasing ROS and preventing oxidative damage .…”
Section: Discussionsupporting
confidence: 79%
“…14 Recent studies have also shown pharmacological effects of IBS on hyperuricemia, oxidative stress, inammation, lipid metabolism and metabolic syndrome. 15,16 In solution IBS has two interconvertible structures, the 1H-and 2H-tautomers, that differ from one to another by the relative position of a proton in the tetrazole ring (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] Relevant studies of poor clinical outcome subtypes of hypertension, such as resistant hypertension 21 and non-dipper hypertension, 22 have observed greater NLR values compared with the standard subtype of hypertension; these results appear to support the opinion that the NLR could be used for risk stratification. High-risk hypertensive patients benefited from diminishing oxidative stress in a recent clinical trial, 35 proving the relationship between inflammation and risk from a clinical application point of view. NLR values may be applied to the risk stratification of hypertension if the results of the present study are confirmed in future follow-up studies, and their further application may offer a chance to improve our understanding of pathophysiology and improve treatment for high risk hypertension.…”
Section: Discussionmentioning
confidence: 99%